Information Design and its relevance to Information Science - Dias Barreira e Oliveira, Joao Augusto [UNESP]; Vicentini Jorente, Maria Jose [UNESP] (Univ Federal Santa Catarina, 2019)
The social, scientific and technological advances have determined transformations in the informational processes. The problem is to understand the need to present and represent visual information effectively and efficiently. It looks for contributions of Information Design, little explored in Information Science, and aims to determine a concept that allows the deepening and scientific, academic and professional updating around the thematic, through theoretical, exploratory, bibliographical and documentary research based on a literature review. The results found seek to open horizons to raise interest of the scientific community for the theme, promote the debate about Information Design and the effective and efficient presentation of information for society. The thematic provides knowledge to act proactively in the visual presentation in informational environments, which can result in significant advances for the disciplines and the users.
Keywords: Information Design; Information Science; Information presentation